Photoluminescence in amorphous TiO2-PbO systems - Leite, E. R.; Carreno, NLV; Santos, LPS; Rangel, J. H.; Soledade, LEB; Longo, Elson [UNESP]; Campos, CEM; Lanciotti, F.; Pizani, P. S.; Varela, José Arana [UNESP] (Springer, 2001)
Photoluminescence (PL) at room temperature has been achieved in amorphous thin films and powders of the TiO2-PbO system. They were prepared by the polymeric precursor method with [PbO]/[TiO2] molar ratios ranging from 0.0 to 1.0. The energy position of maximum PL emission and the PL intensity showed dependence on Pb concentration. The Pb addition suggests an increase in the number of nonbridging oxygens (NBO) in the amorphous TiO2 network. These results support the relationship between photoluminescence and structure in TiO2-based amorphous materials.